2018
DOI: 10.1103/physrevfluids.3.024601
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the flow in the wake of a stationary sphere immersed in a turbulent boundary layer

Abstract: In many applications, finite-sized particles are immersed in a turbulent boundary layer (TBL) and it is of interest to study wall effects on the instantaneous shedding of turbulence structures and associated mean velocity and Reynolds stress distributions. Here, 3D flow field dynamics in the wake of a prototypical, small sphere (D + = 50, 692 < Re D < 959) placed in the TBL's outer, logarithmic, and buffer layer, were measured using time-resolved tomo-PIV. Increasing wall proximity increasingly tilted the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
(111 reference statements)
3
20
1
Order By: Relevance
“…2010), and the data quality was assessed by evaluating the residual of the continuity equation for an incompressible fluid, ( values exceeded 0.87, see also van Hout et al. 2018).…”
Section: Experimental System and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…2010), and the data quality was assessed by evaluating the residual of the continuity equation for an incompressible fluid, ( values exceeded 0.87, see also van Hout et al. 2018).…”
Section: Experimental System and Data Processingmentioning
confidence: 99%
“…This is not expected to remove any relevant large-scale flow structures in the sphere wake. Spatial velocity gradients were based on the locally fitted quadratic regression (Elsinga et al 2010), and the data quality was assessed by evaluating the residual of the continuity equation for an incompressible fluid, ∂U i /∂x i = 0 (R 2 values exceeded 0.87, see also van Hout et al 2018).…”
Section: Experimental System and Data Processingmentioning
confidence: 99%
“…The mean lift forces simulated for spheres with 1.78 ≤ d + /2 ≤ 12.47 centered at a wall-normal location y + = 17.31 from the wall at Re τ = 178.12 were negative in all cases. In this context, tomographic PIV performed by van Hout et al (2018) also suggested a negative lift contribution on a tethered sphere with d + /2 = 25 centered at y + = 43 above the wall at Re τ = 352 due to the sphere wake tilting away from the wall. Under both studies, the gaps between the wall and the bottom sphere were 4.84 ≤ y + ≤ 18.…”
Section: Introductionmentioning
confidence: 88%
“…The mean lift forces simulated for spheres with 1.78 ≤ d + /2 ≤ 12.47 centered at a wallnormal location y + = 17.31 from the wall at friction Reynolds number, Re τ = 178.12 were negative in all cases. Tomographic PIV performed by van Hout et al (2018) at Re τ = 352 downstream of a tethered sphere with d + /2 = 25 centered at y + = 43 above the wall also suggested a negative lift contribution due to the sphere wake tilting away from the wall. By contrast, Hall (1988), who measured the mean lift force acting on a stationary particle lying on the wall in a turbulent boundary layer using a force transducer, reported a positive lift contribution.…”
Section: Introductionmentioning
confidence: 91%